Ischemic stroke in childhood: A Senegalese cohort - Ndiaye, Moustapha; Seck, Lala Bouna; Basse, Anna Modji; Sow, Adjaratou Dieynaba; Fogany, Yannick; Fall, Lamine; Touré, Kamadore; Sène, Marème Soda; Diagne, Ngor Side; Ba, Idrissa; Diop, Amadou Gallo; Sow, Hussein Dembel; Ndiaye, Mouhamadou Mansour (Journal of Pediatric Neurology, 2013)
Ischemic stroke is infrequent in childhood. Etiological factors depend on epidemiological context. The purpose of this study is to determine risk factors, clinical and radiological features and outcome of arterial ischemic stroke in a cohort of Senegalese infants. We carried out a retrospective study of medical data of children hospitalized with arterial ischemic stroke in the neurological department of Fann teaching hospital and at Children's Hospital Albert Royer, from July 2003 to July 2011. Forty-eight cases were included in this study with ages ranging from 2 months to 18 yr, with a female/male ratio of 0.71. Mean age at the time of occurrence stroke was 89.37 mo. The most common symptoms were hemiparesis (93.75%), motor partial seizures (24.44%), and Broca's aphasia (33.3%). The middle cerebral artery was mostly affected (87.5%). Risk factors were predominantly sickle cell disease, anemia, embolic heart disease, meningoencephalitis and head trauma. 8.33% of patients died. After discharge, 16.66% of patients were lost follow-up and 62.5% of the total cohort had neurological impairments. Treatment was essentially symptomatic and secondary prevention was provided by treatment with anticoagulants or anti-platelets agents depending on the etiology of ischemic stroke.
Keywords: Ischemic stroke; childhood